Characterizing the setting of cement when mixed with cork, blue gum, or maritime pine, grown in Portugal - II: X-ray diffraction and differential thermal analyzes - Pereira, Catarina; Jorge, Fernando Caldeira; Irle, Mark; Ferreira, Jose Maria (JOURNAL OF WOOD SCIENCE, 2006)
It is already known by the scientific and industrial communities that lignocellulosic substrates are, to a certain extent, inhibitors of the hydration reaction of cement. The extent to which and how they influence such reactions is still a matter of debate. Several techniques, such as calorimetry, i.e., the measurement of the heat evolved or obtaining temperature profiles during the hydration, the determination of extractive contents of lignocellulosic substrates and their relation with the characteristics of the hydration curves, or even testing of the mechanical properties of the wood-cement composites, have been used in previous research. This study complements past research using two techniques that have been used in the analysis of cement hydration but are not usually applied to lignocellulose-cement mixes, namely X-ray diffraction (XRD) and differential thermal analysis (DTA). The raw materials for this study were three lignocellulosic materials of Portuguese origin: cork (the bark of Quercus suber L.), blue gum (Eucalyptus globulus Labill.), and maritime pine (Pinus pinaster Ait); and Portland cement. The two techniques allowed tracking of the evolution of the main cement constituents during hydration. It was found that all the lignocellulosic substrates had detrimental effects on cement hydration. The blue gum exhibited the fastest hydration kinetics in the initial stage of reaction, but was then overtaken by cork, which at the end gave the highest hydration conversion amongst the three lignocellulosic substrates. Although pine caused the slowest initial hydration kinetics, with the passage of time its effect approached that of blue gum. At the end of the hydration period, specimens containing either species had similar quantities of hydration reaction products. The DTA and XRD results were consistent and are in good agreement with the temperature profiles and compatibility indexes reported in a previous work.
Keywords: cement; Cork; differential thermal analysis; Wood; X-ray diffraction

Characterizing the setting of cement when mixed with cork, blue gum, or maritime pine, grown in Portugal - II: X-ray diffraction and differential thermal analyzes - Pereira, Catarina; Jorge, Fernando Caldeira; Irle, Mark; Ferreira, Jose Maria (JOURNAL OF WOOD SCIENCE, 2006)
It is already known by the scientific and industrial communities that lignocellulosic substrates are, to a certain extent, inhibitors of the hydration reaction of cement. The extent to which and how they influence such reactions is still a matter of debate. Several techniques, such as calorimetry, i.e., the measurement of the heat evolved or obtaining temperature profiles during the hydration, the determination of extractive contents of lignocellulosic substrates and their relation with the characteristics of the hydration curves, or even testing of the mechanical properties of the wood-cement composites, have been used in previous research. This study complements past research using two techniques that have been used in the analysis of cement hydration but are not usually applied to lignocellulose-cement mixes, namely X-ray diffraction (XRD) and differential thermal analysis (DTA). The raw materials for this study were three lignocellulosic materials of Portuguese origin: cork (the bark of Quercus suber L.), blue gum (Eucalyptus globulus Labill.), and maritime pine (Pinus pinaster Ait); and Portland cement. The two techniques allowed tracking of the evolution of the main cement constituents during hydration. It was found that all the lignocellulosic substrates had detrimental effects on cement hydration. The blue gum exhibited the fastest hydration kinetics in the initial stage of reaction, but was then overtaken by cork, which at the end gave the highest hydration conversion amongst the three lignocellulosic substrates. Although pine caused the slowest initial hydration kinetics, with the passage of time its effect approached that of blue gum. At the end of the hydration period, specimens containing either species had similar quantities of hydration reaction products. The DTA and XRD results were consistent and are in good agreement with the temperature profiles and compatibility indexes reported in a previous work.
The following values have no corresponding Zotero field: pub-location: 3-3-13, HONGO, BUNKYO-KU, TOKYO, 113-0033, JAPAN publisher: SPRINGER TOKYO
Keywords: cement; Cork; differential thermal analysis; Wood; X-ray diffraction

Influence of granule properties and concentration on cork-cement compatibility - Karade, Sukhdeo R.; Irle, Mark; Maher, Kevin (Holz als Roh- und Werkstoff, 2006)
Cork granules are produced as by-products and waste by the cork processing industries that make ‘bottle stoppers’ as a main product. These granules are of low density and could be used as lightweight aggregates for making concrete. This paper describes an investigation carried out to assess the compatibility of cork granules with cement for the manufacture of lightweight cementitious composites. Five different grades of cork granules varying in terms of size and density were investigated. The effects of extractives, particle size and density of the cork granules were studied. The results indicate that these parameters affect cement hydration in a complex way. At lower concentrations of cork (10%), only the extractives have an inﬂuence on hydration behaviour. At higher cork concentrations (20% and 30%), however, particle size and density also affect the compatibility. Nevertheless, cork granules are found to be compatible with cement.
Keywords: cement; composites; Cork granules; Density; hydration (voyant)

Influence of granule properties and concentration on cork-cement compatibility - Karade, Sukhdeo R; Irle, Mark; Maher, Kevin (Holz als Roh- und Werkstoff, 2006)
Cork granules are produced as by-products and waste by the cork processing industries that make ‘bottle stoppers’ as a main product. These granules are of low density and could be used as lightweight aggregates for making concrete. This paper describes an investigation carried out to assess the compatibility of cork granules with cement for the manufacture of lightweight cementitious composites. Five different grades of cork granules varying in terms of size and density were investigated. The effects of extractives, particle size and density of the cork granules were studied. The results indicate that these parameters affect cement hydration in a complex way. At lower concentrations of cork (10%), only the extractives have an inﬂuence on hydration behaviour. At higher cork concentrations (20% and 30%), however, particle size and density also affect the compatibility. Nevertheless, cork granules are found to be compatible with cement.
Keywords: cement; composites; Cork granules; Density; hydration (voyant)

Adsorption of Cations from a Cement Suspension onto Lignocellulosic Substrates and its Influence on Cement Setting - Pereira, C.; Caldeira Jorge, F.; Ferreira, J. M. F. (Journal of Wood Chemistry and Technology, 2005)
Abstract The calcium (Ca), sodium (Na), and potassium (K) contents of blue gum, maritime pine, and cork increased after these lignocellulosics were stirred with the filtrate of a cement suspension or a solution of calcium hydroxide. The adsorbed cations could be released easily by treatment with an acidic solution. It is suggested that those raw materials, and lignocellulosics in general, act as cation exchange substrates when they are mixed with cement and water to make wood?cement composites. The implications that such phenomena may have on cement hardening reactions, and how they could hinder them are discussed. The possibility that the phenomenon is related to well?known compatibility problems that many woods present when manufacturing wood?cement composites is discussed.
doi: 10.1080/02773810500366672doi: 10.1080/02773810500366672The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Adsorption; cations; cement; hindrance; interactions; lignocellulosics

Adsorption of Cations from a Cement Suspension onto Lignocellulosic Substrates and its Influence on Cement Setting - Pereira, C; Caldeira Jorge, F; Ferreira, J M F (Journal of Wood Chemistry and Technology, 2005)
Abstract The calcium (Ca), sodium (Na), and potassium (K) contents of blue gum, maritime pine, and cork increased after these lignocellulosics were stirred with the filtrate of a cement suspension or a solution of calcium hydroxide. The adsorbed cations could be released easily by treatment with an acidic solution. It is suggested that those raw materials, and lignocellulosics in general, act as cation exchange substrates when they are mixed with cement and water to make wood?cement composites. The implications that such phenomena may have on cement hardening reactions, and how they could hinder them are discussed. The possibility that the phenomenon is related to well?known compatibility problems that many woods present when manufacturing wood?cement composites is discussed.
doi: 10.1080/02773810500366672
Keywords: Adsorption; cations; cement; hindrance; interactions; lignocellulosics

A new technique to classify the compatibility of wood with cement - Hachmi, M; Moslemi, A A; Campbell, A G (Wood science and technology, 1990)
Wood-cement panels have commanded renewed interest during the last decade be- cause of their potential application in the building industry. Several methods to classify wood of various species regarding its compatibility with cement have been established in the literature based on hydration measurements in Dewar flasks. These ranking methods lack consistency in the classification of species because the hydration conditions vary among laboratories. Three techniques for evaluating wood-cement compatibility were established and compared. The best technique is based on a wood-cement compatibility factor which is the ratio of the area under the wood-cement hydration heat rate curve to that of neat cement. The area is calculated on 24-h basis starting from the initial cement set time. This area ratio method ranks species over a 100% scale and accounts well for species that are totally incompatible.
Keywords: cement; hydration; Wood; wood-cement compatibility (voyant); wood-cement panels